B216 Spinal epidural hematoma after epidural block: case analysis of contributing factors and effective management. (11th August 2022) - Sousa, F; Pinho, J; Zuzarte, D; Bernardino, M; Medeiros, L
Abstract : Background and Aims: Spinal hematomas after neuraxial anesthesia can have devastating consequences. Increasing patient frailty may be involved in a growing incidence and early detection remains paramount in successful management. Through analysis of a clinical case, we aimed to identify possible factors involved in the occurrence and early detection of a spinal hematoma during epidural analgesia. Methods: A 76-year-old man with esophageal cancer, diabetes mellitus, obstructive lung disease and smoking history presented for elective esophagectomy. Surgery was performed under general anesthesia and a thoracic epidural block, and the epidural catheter was used for postoperative analgesia. On the third postoperative day, back pain and lower limb weakness prompted a spinal MRI, which revealed a T6-T8 epidural hematoma ( Figure 1 ). Emergency laminectomy was performed, and the neurologic deficits subsided. Patient charts were reviewed and involved anesthetic personnel consulted for case analysis. Results: Epidural placement was difficult and advanced thoracic spine osteoarthritis was later identified on spinal imaging. The postoperative course was also remarkable for euglycemic diabetic ketoacidosis, acidemia may have contributed to impaired epidural hemostasis. Other possible factors identified include preoperative thoracic chemoradiation, insulin-treated diabetes mellitus and frailty syndrome ( Figure 2 ). Importantly, the acute pain service was decisive in expediting diagnosis and management, ultimately resulting in reversal of the neurological deficits. Conclusions: Interaction between otherwise minor risk factors can contribute to spinal epidural hematoma after epidural block. Patient frailty, particularly, may represent an increasingly prevalent risk factor. Timely diagnosis and treatment are of the utmost importance, and acute pain services undoubtedly play a key role in active vigilance.